Politics without Reason - Levine, D. author. aut Link
XI, 207 p.
Keywords: Politics without Reason explores the roots of contemporary hostility toward liberalism. The thesis of the book is that ambivalence about the self and about desire as an expression of the self fosters the intense animosity we observe directed toward the liberal ideal.